Investigating the monetary policy of central banks with assessment indicators - Marcel Bluhm (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
This paper outlines a new method for using qualitative information to analyze the monetary policy strategy of central banks. Quantitative assessment indicators that are extracted from a central bank's public statements via the balance statistic approach are employed to estimate a Taylor-type rule. This procedure allows to directly capture a policymaker's assessments of macroeconomic variables that are relevant for its decision making process. As an application of the proposed method the monetary policy of the Bundesbank is re-investigated with a new dataset. One distinctive feature of the Bundesbank's strategy consisted of targeting growth in monetary aggregates. The analysis using the proposed method provides evidence that the Bundesbank indeed took into consideration monetary aggregates but also real economic activity and inflation developments in its monetary policy strategy since 1975.
urn:nbn:de:hebis:30-115368
Keywords: E52; E58; N14; 330; Monetary Policy Rule; Statement Indicators; Bundesbank; Monetary Targeting; Geldpolitik; Geldmengensteuerung; Zentralbank; Bankbilanz; Monetärer Indikator; Deutschland